Mechanisms of Xenobiotic Receptor Activation: Direct vs. Indirect - Mackowiak, Bryan (Biochim Biophys Acta, 2016)
The so-called xenobiotic receptors (XRs) have functionally evolved into cellular sensors for both endogenous and exogenous stimuli by regulating the transcription of genes encoding drug-metabolizing enzymes and transporters, as well as those involving energy homeostasis, cell proliferation, and/or immune responses. Unlike prototypical steroid hormone receptors, XRs are activated through both direct ligand-binding and ligand-independent (indirect) mechanisms by a plethora of structurally unrelated chemicals. This review covers research literature that discusses direct vs. indirect activation of XRs. A particular focus is centered on the signaling control of the constitutive androstane receptor (CAR), the pregnane X receptor (PXR) and the aryl hydrocarbon receptor (AhR). We expect that this review will shed light on both the common and distinct mechanisms associated with activation of these three XRs.